Student's perception of the use of English in the Campus Enviroment as a Second Language - Putri, Aprilia Dwi; Nurcholis, Ivan Achmad (Jurnal Inovasi Penelitian Ilmu Pendidikan Indonesia, 2025)
This research aims to explore students' perceptions of the use of English as a second language in the campus environment. The choice of this topic is based on the importance of English language skills in the context of globalization and competition in the world of work, as well as the role of English as a lingua franca in the academic environment. This research uses a qualitative approach with survey methods and in depth interviews to collect data. The research instruments used include a questionnaire designed to measure students' perceptions regarding the use of English, as well as an interview guide to gain deeper insight into their experiences. The data analysis technique was carried out using thematic analysis to identify patterns and themes that emerged from the data collected. The results showed that the majority of students had a positive perception of the use of English on campus, considering it an important tool for improving communication skills and access to academic resources. However, there are also challenges faced, such as anxiety in speaking and lack of support from the surrounding environment. The discussion of the results indicates the need to develop more effective English language support programs on campus to increase students' confidence in using English. It is hoped that this research can contribute to the development of language education policies in higher education institutions and increase awareness of the importance of mastering English among students.